PENGARUH HARGA, PROMOSI DAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN BURGER KING KAWASAN SURABAYA PLAZA SURABAYA - Enny Istanti, Enny Istanti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2019)
This study aims to determine the effect of prices, promotions, and products on consumer purchasing decisions simultaneously, partialy, and significantly. And to determine which variables have a dominant influence. Methods of research using quantitative methods in the study population are consumers Restorant Burger King Surabaya Plaza Surabaya. The sampling technique used was simple random sampling and accidental sampling with a sample size of 95 respondents to the formula Slovin. Technique uses multiple linier regression analysis. The variable is the prices, promotions, products, buying decisions. Result were obtained value of F count 31,843 with a significance of 0,000, t value of each variable of prices 2,635 > 1,98638, variable promotions 2,892 > 1,98638, and variable products 3,531 > 1,98638 Based on the result of research in Restorant Burger King Surabaya Plaza Surabaya to the simultaneous effect of three independent variables, partial and significant impact on buying decisions. The Independent variable of Product has a dominant influence on the Purchasing Decision which has a Beta value of 0,351.